Aspects of Shared Decision Making in a Cognitive-Educational Intervention for Family Members of Persons Coping With Severe Mental Illness - Weiss, Penina; Redlich-Amirav, Dorit; Daass-Iraqi, Sara; Hadas-Lidor, Noami (Frontiers in Psychiatry, 2021)
Background: Partnerships and family inclusion are embedded in mental health policies. Shared Decision Making (SDM) is as an effective health communication model designed to facilitate service users and providers engagement in reaching jointly decisions concerning interventions. Keshet is a 15 bi-weekly academic course for family members of people with mental illnesses that enhances positive family cognitive communication skills. Purpose of study: To exhibit how SDM is inherently expressed in Keshet. Method: We conducted a secondary analysis of previous Keshet evaluation studies and course protocols that focused on revealing SDM use. Additionally, we conducted a pilot evaluation study directly targeting SDM use by Keshet moderators and participants before and after the course. Results: SDM was found to be a prominent feature in Keshet interventions. Pilot study results point to a significant improvement in SDM use following Keshet. Following participation in the program, making decisions jointly was found to be a prominent feature. Conclusions: Interventions such as Keshet that include an SDM approach can contribute to the integration of academic, professional and ‘lived experience’ within a shared perspective, thus promoting an enhanced equality- based SDM model that benefits individuals as well as mental health systems.